2016
DOI: 10.1111/nmo.12936
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin in saliva as a biomarker for oropharyngeal reflux compared with 24‐hour esophageal impedance/pH monitoring in pediatric patients

Abstract: NCT01091805.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 47 publications
(133 reference statements)
2
48
0
4
Order By: Relevance
“…Potluri et al used the fibrinogen digestion method to compare saliva/sputum pepsin assay with 24‐hour esophageal pH monitoring, for detection of gastric reflux into the proximal esophagus, oropharynx, and lungs. Several different assays for detecting pepsin in saliva/sputum, including Western blot and enzyme‐linked immunosorbent assay, have been used in the lab. However, these methods are both laborious and time consuming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potluri et al used the fibrinogen digestion method to compare saliva/sputum pepsin assay with 24‐hour esophageal pH monitoring, for detection of gastric reflux into the proximal esophagus, oropharynx, and lungs. Several different assays for detecting pepsin in saliva/sputum, including Western blot and enzyme‐linked immunosorbent assay, have been used in the lab. However, these methods are both laborious and time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…A positive PPI response after treatment further confirmed the diagnosis of LPR in good responders. With regard to the collection of saliva/sputum samples, Fortunato el al . discovered that the concentration of salivary/sputum pepsin had covered a wide range when observed in individuals over 24 hours, and that saliva/sputum samples must be obtained soon after a reflux event.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our study may include our center's interpretation of pH‐MII studies. Several centers vary their positive criteria for reflux regarding number of events and symptom correlation due to a lack of standardized metrics in pediatrics . This study demonstrated that pH‐MII‐defined GERD diagnosis was higher, perhaps up to 2× the prevalence of the general population, but still overall relatively low regarding diagnostic yield.…”
Section: Discussionmentioning
confidence: 84%
“…This study demonstrated that pH‐MII‐defined GERD diagnosis was higher, perhaps up to 2× the prevalence of the general population, but still overall relatively low regarding diagnostic yield. If other published standards, such as 72 events were used, in this study for children >1 year of age, the diagnosis of GERD or excessive esophageal acid exposure using pH‐MII may have been lower . Finally, this study primarily looked at the reflux evaluation and not the other components of aerodigestive care.…”
Section: Discussionmentioning
confidence: 99%
“…The first insight that can be found in literature, concerning the possible involvement of ENT anatomical structures in the reflux pathology, goes back to 1903; in fact, Coffin speculated "gas reflux from the stomach" as well as the "hyper-acidity" could be considered responsible for hoarseness and back rhinorrhea [1][2][3][4]. Starting from the '80s, besides the relatively "old" knowledge of GED, a new concept arose; it proposed LPR could have been caused by "acid vapors" action, coming from the stomach.…”
Section: Introductionmentioning
confidence: 99%